Chronic isolation stress predisposes the frontal cortex but not the hippocampus to the potentially detrimental release of cytochrome c from mitochondria and the activation of caspase-3 - Filipović, Dragana; Zlatković, J.; Inta, Dragos; Bjelobaba, I.; Stojiljkovic, M.; Gass, Peter (Journal of neuroscience research, 2011)
Mitochondria are central integrators and transducers of proapoptotic signals for neuronal apoptosis. The tumor suppressor protein p53 can trigger apoptosis independently of its transcriptional activity, through subcellular translocation of cytochrome c and caspase activation. To define better the proapoptotic role of p53 under various stress conditions, we investigated the protein levels of p53 and cytochrome c in mitochondrial and cytosolic fractions, as well as caspase-3 activation and apoptosis, in the prefrontal cortex and hippocampus of male Wistar rats subjected to acute, chronic, or combined stressors. Mitochondrial p53 can suppress the antioxidant enzyme MnSOD, so its activity was also determined. In the prefrontal cortex, but not in hippocampus, increased protein levels of p53 were found in mitochondria, leading to cytochrome c release into cytoplasm, activation of caspase-3, and apoptotic cell death following combined stressors. Decreased mitochondrial MnSOD activity following combined stressors in both brain structures indicated a state of oxidative stress. This suggests that chronic isolation stress compromises mitochondrial MnSOD activity in both the prefrontal cortex and the hippocampus but likely results in mitochondrial-triggered proapoptotic signaling mediated by a transcription-independent p53 mechanism only in the prefrontal cortex. Thus, our data demonstrate a tissue-specific (prefrontal cortex vs. hippocampus) response to applied stressors. © 2011 Wiley-Liss, Inc.
Gesehen am 27.10.2022